The Effect of Using Two Stay Two Stray Technique on Students Writing Skill of Recount Text at Eighth Grade SMPN 37 Medan - Calonroiboto Hutauruk; Carolina Pakpahan; Febrika Dwi Lestrai Lumban Toruan (Education Achievement: Journal of Science and Research, 2024)
This research aimed to find out the effect on students' writing skills by using Two Stay- Two Stray Technique. The research design of this study was experimental quantitative. The eight grade students in Smpn 37 Medan were chosen as the sample of this study with a total number of 46 students. The experimental and control classes employed pre-tests and post-tests. These tests proved in the form of writing test. The data on the tests were calculated by using the t-test formula. The result showed that the post-test score was higher than the pre-test. The finding showed that there was an effect significantly on the students’ writing skills after treatment. There was enchantment of the student's number score. The mean score of the experimental class range from the pre-test was 58,5 and the post-test 79,5 and for the control class the mean score pre-test was 59,2 and from the post-test was 71,6. Thus Two Stay Two Stray Technique could be used as one of the alternatives to teaching writing recount text for Eight Grade of SMPN 37 Medan.